Passabilidade e possibilidades - RODRIGUES, Júlia Naomí Costa (2023)
It is guided, without prior knowledge, concepts that distort and discriminate transsexuality, forging a collective imaginary that dictates, or tries to dictate, what a trans person would be like, that is, the stereotype, which willingly or not, draws a comparative border between the cisgender and transgender, where cisgender would be a kind of identity legality so that other sexual identities would be illegitimate. Such a comparative frontier made trans people (transsexuals and transvestites) seek adaptation to the cisgender “model”, which gave rise to the term designated as passability, which can be translated into how much a trans person looks like, or passes for cisgender, a concept based on in the image, where appearance dictates who can or cannot access spaces and rights, becoming habeas corpus to live in society without suffering violence, violations, discrimination, prejudice and sanctions. However, what could be seen as a way out of so many mishaps can also be seen as a trap that puts trans people in the condition of having to look like someone else in order to exist, and exacerbates the various difficulties faced by those trans people who are not considered passable emphasizing the intersection between transsexuality, race and gender, clippings that cross and leave marks on trans bodies, observed as prohibited, public and desirable when convenient. In this sense, the present study sought to analyze the discourses of transgender people (transsexuals and transvestites) and cisgender people about “passability” as a strategy to defend transphobia, aiming to problematize the historical conditions for the emergence of “passability” in the trans community; understand the meanings given to “passability” by trans and cis people; and point out the intersections between gender, race and sexual orientation in the use of “passability”. For this, a qualitative research was carried out, interviewing six transgender people (three transsexual/transvestite women and three trans/transmasculine men) and six cisgender people (three men and three women), totaling twelve people, cisgender and transgender from the city of São Luís do Maranhão, through a semi-structured questionnaire, in which the interviews were recorded and faithfully transcribed, based on the archeogenealogical method, inspired by Foucault, to carry out the data analysis. It was noted, therefore, firstly, the change in the conceptual perception of transsexuality in the trans and cis perspectives, while passability has been losing its obligatory bias for trans people, although it is still perceived the need for this, not only access to social spaces, but also to well-being, self-esteem, safety and self-care. In the intersectionality of race and gender in the trans community, the most stigmatized people, a priori, are black trans women. It was also observed that passability is present and decisive, also in cisgenderism, with criteria different from those required in transgenderism, since the cis body is socially “acceptable”, and origin, education and clothing (among others). Finally, the study goes beyond passability, talks about human lives and citizenship, and presents itself as a motivation for new studies that may bring more discussions on this and other topics that address transsexuality.